Nearshore Pelagic Microbial Community Abundance Affects Recruitment Success of Giant Kelp, Macrocystis pyrifera - Morris, Megan M.; Haggerty, John M.; Papudeshi, Bhavya N.; Vega, Alejandro A.; Edwards, Matthew S.; Dinsdale, Elizabeth A. (Frontiers in Microbiology, 2016)
Marine microbes mediate key ecological processes in kelp forest ecosystems and interact with the macroalgae. Pelagic and biofilm-associated microbes interact with macroalgal propagules at multiple stages of recruitment, yet these interactions have not been described for M. pyrifera. Here we investigate the influence of microbes from coastal environments on recruitment of giant kelp, Macrocystis pyrifera. Through repeated laboratory experiments we tested the effects of altered pelagic microbial abundance on the settlement and development of the microscopic propagules of M. pyrifera during recruitment. M. pyrifera zoospores were reared in laboratory microcosms exposed to environmental microbial community seawater source, throughout the complete haploid stages of the recruitment cycle, including zoospore release, followed by zoospore settlement, to gametophyte germination and development. We altered the microbial abundance states differentially in three independent experiments with repeated trials, where microbes were a) present or absent in seawater, b) altered in community composition, and c) altered in abundance. Within the third experiment, we also tested the effect of nearshore versus offshore microbial communities on the macroalgal propagules. Distinct pelagic microbial communities were collected from two southern California temperate environments reflecting contrasting intensity of human influence, the nearshore Point Loma kelp forest and the offshore Santa Catalina Island kelp forest. The Point Loma kelp forest is a high impacted coastal region adjacent to the populous San Diego Bay; whereas the kelp forest at Catalina Island is a low impacted region of the Channel Islands, 40 kilometers offshore the southern California coast, and is adjacent to a marine protected area. Kelp gametophytes reared with nearshore Point Loma microbes showed lower survival, growth, and deteriorated morphology compared to gametophytes with the offshore Catalina Island microbial community, and these effects were magnified under high microbial abundances. Reducing abundance of Point Loma microbes restored M. pyrifera propagule success. Yet an intermediate microbial abundance was optimal for kelp propagules reared with Catalina Island microbes, suggesting that microbes also have a beneficial influence on kelp. Our study shows that pelagic microbes from nearshore and offshore environments are differentially influencing kelp propagule success, which has significant implications for kelp recruitment and kelp forest ecosystem health.